PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROYEK TERHADAP KEMAMPUAN MERANCANG PRODUK DIFUSI OSMOSIS - Syamsul Bahri; Hilda Zulkifli; Kodri Madang (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2019)
This study aims to develop a project-based Student Worksheet (LKPD) on the ability to design osmosis diffusion products for vocational students in Tourism Expertise. This research includes the development of LKPD which is divided into three phases, namely a preliminary study phase, a product design development phase, and a product testing phase. The results showed that the LKPD that had been developed was feasible used well in learning and fulfilled the validation test by experts for the feasibility of the material (content), presentation (construction) and language with good categories. Student responses after using LKPD are very good for supporting and completing LKPD while learning. LKPD tested in Applied Science lessons was able to improve student scores from initial test results with an average score of 66.5 and final test results with an average score of 75.4.